Spatial interpolation enables normative data comparison in gaze-contingent microperimetry - Denniss, Jonathan; Astle, Andrew T. (ARVO, 2016)
Purpose: To demonstrate methods that enable visual field sensitivities to be compared with normative data without restriction to a fixed test pattern.